A Review of Ecological Engineering in Pest Management: A Multidisciplinary and Sustainable Approach - Kumar, Pavan; Kumar, Deepak; Sharma, Preeti; Monika; Vandana; Priyanka; Arvind (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2025)
The agricultural revolution has led to ecosystem instability and a lack of natural pest management. Ecological engineering aims to maintain a balanced agroecosystem by strategically manipulating crops and habitats to enhance the survival of natural enemies while limiting pest populations. Push-pull strategies are adopted in ecological engineering by using semiochemicals and trapping crops. Natural enemies are conserved by providing alternate foods through chocolate-box ecology and beetle-bank feeding and pest movement has been arrested through windbreaks and trenches.